Development of an effective and safe topical anti-inflammatory gel containing Jatropha gossypiifolia leaf extract: Results from a pre-clinical trial in mice. (5th December 2018) - Xavier-Santos, Jacinthia B.; Félix-Silva, Juliana; Passos, Júlia G.R.; Gomes, Jacyra A.S.; Fernandes, Júlia M.; Garcia, Vinícius Barreto; de Araujo-Junior, Raimundo Fernandes; Zucolotto, Silvana M.; Silva-Junior, Arnóbio A.; Fernandes-Pedrosa, Matheus F.
Abstract: Ethnopharmacological relevance: Jatropha gossypiifolia L. (Euphorbiaceae) is a medicinal plant widely used in traditional medicine as an anti-inflammatory remedy. The topical use of the leaves and/or aerial parts of this plant as anti-inflammatory, analgesic, wound healing and anti-infective in several skin diseases is a common practice in many countries. The use of baths or dressings with this vegetal species is frequently reported in folk medicine. Aim of the study: To evaluate the topical anti-inflammatory of aqueous extract from leaves of J. gossypiifolia and to develop a safe and effective herbal gel with anti-inflammatory potential. Material and methods: First, the topical acute anti-inflammatory activity of J. gossypiifolia extract was evaluated in ear edema induced by single application of croton oil in mice. Then, a polaxamer-based gel containing J. gossypiifolia extract was developed, physicochemically characterized and evaluated in the same model of inflammation to assess whether the extract incorporation in gel would affect its anti-inflammatory potential. The best formulation was then assayed in ear edema induced by multiple applications of croton oil in mice, to evaluate its chronic anti-inflammatory potential. Inflammatory parameters evaluated included edema, nitrite concentration, mieloperoxidase (MPO) activity and oxidative damage in lipids and proteins. Finally, dermal irritation/corrosion test in mice was performed to access the safeness of the developed gel. Phytochemical characterization of J. gossypiifolia extract was performed by high performance liquid chromatography with diode array detector (HPLC-DAD) analysis. Results: J. gossypiifolia showed significant acute anti-inflammatory activity in ear edema model, and this activity was significantly increased when equivalent amounts of extract was applied incorporated in the developed polaxamer gels. The gels containing different amounts of extract reduced significantly the levels of edema, nitrite and MPO enzyme in mice ears, with intensity similar to the anti-inflammatory standard drug dexamethasone. The gel containing 1.0% of extract was further evaluated and also showed significant anti-inflammatory activity in chronic inflammation test, reducing significantly ear edema, lipid peroxidation and depletion of reduced glutathione, similarly to dexamethasone. Placebo formulation as well as gel containing extract showed pH compatible to that of human skin and exhibited absence of signs of toxicity in mice, indicating the safeness of the developed product for topical use. HPLC analysis confirmed the presence of C -glycosylflavonoids (orientin, isoorientin, vitexin and isovitexin) as the major compounds of J. gossypiifolia aqueous leaf extract. Conclusions: The results demonstrate the potentiality of J. gossypiifolia gel as a promising safe and effective topical anti-inflammatory agent for treatment of cutaneous inflammatory diseases. Graphical abstract: